2003
DOI: 10.1039/b306874a
|View full text |Cite
|
Sign up to set email alerts
|

Monomeric (dialkylamino)boranes: a new and efficient boron source in palladium catalyzed C–B bond formation with aryl halides

Abstract: Thermal decomposition of hindered amine-borane adducts leads in high yields to monomeric (dialkylamino)boranes R1R2N-BH2 (R1 and R2 = alkyl) that are new and efficient boron-sources in the Pd0 catalyzed borylation reaction affording monomeric aryl(dialkylamino)boranes R1R2N-BHR3 (R3 = aryl).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 25 publications
2
61
0
1
Order By: Relevance
“…20,23,24 Interestingly, during the same period, G. Alcaraz et al had demonstrated interest in dialkylaminoboranes R 2 NBH 2 in pallado-catalyzed reactions. 33 By comparison, it is worth noting that in silane chemistry, the use of dihydrogenosilanes R 2 SiH 2 in place of tertiary hydrogenosilanes HSiR 3 led us to the discovery of Ru 2 H 4 (µ-η 2 :η 2 :η 2 :η 2 -SiH 4 )(PCy 3 ) 4 , the first complex incorporating the simplest silane trapped between two metals. 34 The stabilization occurred through multiple σ-Si-H bond interactions.…”
Section: Synthesis Of New Bis(dihydrogen) Complexes the Firstmentioning
confidence: 99%
“…20,23,24 Interestingly, during the same period, G. Alcaraz et al had demonstrated interest in dialkylaminoboranes R 2 NBH 2 in pallado-catalyzed reactions. 33 By comparison, it is worth noting that in silane chemistry, the use of dihydrogenosilanes R 2 SiH 2 in place of tertiary hydrogenosilanes HSiR 3 led us to the discovery of Ru 2 H 4 (µ-η 2 :η 2 :η 2 :η 2 -SiH 4 )(PCy 3 ) 4 , the first complex incorporating the simplest silane trapped between two metals. 34 The stabilization occurred through multiple σ-Si-H bond interactions.…”
Section: Synthesis Of New Bis(dihydrogen) Complexes the Firstmentioning
confidence: 99%
“…[44] Also, amine-boranes are attracting considerable attention as potential hydrogen-storage materials. [45] Primary and secondary amine-borane adducts have previously been thermally dehydrocoupled at elevated temperatures (> 100 8C) to give cyclic aminoboranes [(R 2 BÀNR' 2 ) x ] (x = 2 or 3) and borazine [(RBÀNR') 3 ] derivatives.…”
Section: Catalytic Dehydrocoupling Of Group 13/group 15 Lewis Acid-bamentioning
confidence: 99%
“…Recently, we demonstrated the excellent ability of monomeric aminoboranes to react as BH sources for C sp 2 -B sp 2 bond formation in a metal-catalyzed process [12]. For our purpose, we naturally envisaged applying our palladium-catalyzed borylation reaction to 1-alkenyl halides.…”
Section: Resultsmentioning
confidence: 97%